209k views
3 votes
Find the general solution to the equation y" – y' – 2y=-et

User Aardbol
by
5.2k points

1 Answer

6 votes


y''-y'-2y=-e^t

The corresponding homogeneous ODE is


y''-y'-2y=0

with characteristic equation


r^2-r-2=(r-2)(r+1)=0

with roots at
r=2 and
r=-1, so the characteristic solution is


y_c=C_1e^(2t)+C_2e^(-t)

For the non-homogeneous ODE, assume a particular solution of the form


y_p=ae^t


\implies{y_p}'=ae^t


\implies{y_p}''=ae^t

Substituting
y_p and its derivatives into the ODE gives


ae^t-ae^t-2ae^t=-e^t


-2ae^t=-e^t


\implies-2a=-1\implies a=\frac12

Then the ODE has the general solution


\boxed{y(t)=C_1e^(2t)++C_2e^(-t)+\frac12e^t}

User Maxisme
by
5.3k points